Rhizodegradation: The plant root exudate and microbial community relationship - Yang K.M. (2023)
Understanding the interaction of plants and microbes during rhizodegradation of organic contaminants is critical for developing effective bioremediation technologies. Plant secretes about 20% of their fixed carbons from photosynthesis into their root zone in the forms of sugar, amino acids, phenolics, flavonoids, and many other compounds. These chemical cocktails of plant metabolites, also known as root exudates, provide a viable nutrient source for soil microbial communities where nutrient availability is known to be limited. In general, contaminant concentration in the environment is inversely correlated to the concentration of plant root exudates. There are higher microbial biomass and contaminant transformation rate as root exudates promote microbial growth and catabolic activities. Due to this evidence, environmental scientists sought to figure out the suitable plant-microbe pairs that show the highest remediation capability suited to the specific organic contaminants.